Giant Enhancement in the Supercapacitance of NiFe–Graphene Nanocomposites Induced by a Magnetic Field - Romero, Jorge; Prima-Garcia, Helena; Varela, Maria; Miralles, Sara G.; Oestreicher, Víctor; Abellán, Gonzalo; Coronado, Eugenio (Advanced Materials, 2019)
The rapid rise in energy demand in the past years has prompted a search for low-cost alternatives for energy storage, supercapacitors being one of the most important devices. It is shown that a dramatic enhancement (≈1100%, from 155 to 1850 F g −1 ) of the specific capacitance of a hybrid stimuli-responsive FeNi 3 –graphene electrode material can be achieved when the charge/discharge cycling is performed in the presence of an applied magnetic field of 4000 G. This result is related to an unprecedented magnetic-field-induced metal segregation of the FeNi 3 nanoparticles during the cycling, which results in the appearance of small Ni clusters (<5 nm) and, consequently, in an increase in pseudocapacitive sites. The results open the door to a systematic improvement of the capacitance values of hybrid supercapacitors, while moving the research in this area towards the development of magnetically addressable energy-storage devices.
CRIS-Team Scopus Importer:2019-05-28
Keywords: magnetic materials; metal segregation; nanocomposites; supercapacitors